2008
DOI: 10.1038/ng.274
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association yields new sequence variants at seven loci that associate with measures of obesity

Abstract: Obesity results from the interaction of genetic and environmental factors. To search for sequence variants that affect variation in two common measures of obesity, weight and body mass index (BMI), both of which are highly heritable, we performed a genome-wide association (GWA) study with 305,846 SNPs typed in 25,344 Icelandic, 2,998 Dutch, 1,890 European Americans and 1,160 African American subjects and combined the results with previously published results from the Diabetes Genetics Initiative (DGI) on 3,024… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,092
7
31

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,234 publications
(1,197 citation statements)
references
References 35 publications
51
1,092
7
31
Order By: Relevance
“…(2010), who failed to find a significant effect of a KCTD15 polymorphism previously associated with obesity in AN patients; as well as with several GWAS, which have not identified any KCTD15 SNP related to AN risk (Boraska et al., 2014; Hinney et al., 2017; Wang et al., 2011). In this regard, several loci in or near KCTD15 have repeatedly been associated with obesity in a number of GWAS and replication studies (Mei et al., 2012; Paternoster et al., 2011; Thorleifsson et al., 2009; Willer et al., 2009). The cerebral location of the gene indicates that its association with weight increase would likely be based on changes in feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…(2010), who failed to find a significant effect of a KCTD15 polymorphism previously associated with obesity in AN patients; as well as with several GWAS, which have not identified any KCTD15 SNP related to AN risk (Boraska et al., 2014; Hinney et al., 2017; Wang et al., 2011). In this regard, several loci in or near KCTD15 have repeatedly been associated with obesity in a number of GWAS and replication studies (Mei et al., 2012; Paternoster et al., 2011; Thorleifsson et al., 2009; Willer et al., 2009). The cerebral location of the gene indicates that its association with weight increase would likely be based on changes in feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, SH2B1 encodes a Src homology adaptor protein involved in leptin and insulin signaling. 25,26 Common variants near this locus are associated with BMI, serum leptin, and body fat in genome-wide association studies (GWASs), [27][28][29][30] while rare dominant mutations have been reported to cause obesity, social isolation, aggressive behavior, and speech and language delay. 31 None of the CNV-contained genes have been associated with ASD or HC defects.…”
Section: Introductionmentioning
confidence: 99%
“…SNP rs11926347, in an intron of ABCC5 (OMIM 60521), and SNP rs6795506, near the 5' end of AHSG (OMIM 138680), had extremely small p-values (Table 8). Among the other nine genes, ADIPOQ (OMIM 605441, 612556) has been widely reported to be associated with obesity and diabetes [21-24]; FNDC3B (OMIM 611909) is involved in positive regulation of adipogenesis [25]; and DGKG (OMIM 601854) and AHSG (OMIM 138680) have been reported to be associated with obesity-related metabolic traits [26,27]. The remaining genes have no reported relation to obesity-related metabolic traits based on our literature review.…”
Section: Resultsmentioning
confidence: 99%